An update on recent progress of the epidemiology, etiology, diagnosis, and treatment of acute septic arthritis: a review - He, Miao; Arthur Vithran, Djandan Tadum; Pan, Linyuan; Zeng, Haijin; Yang, Guang; Lu, Bangbao; Zhang, Fangjie (Frontiers in Cellular and Infection Microbiology, 2023)
Acute septic arthritis is on the rise among all patients. Acute septic arthritis must be extensively assessed, identified, and treated to prevent fatal consequences. Antimicrobial therapy administered intravenously has long been considered the gold standard for treating acute osteoarticular infections. According to clinical research, parenteral antibiotics for a few days, followed by oral antibiotics, are safe and effective for treating infections without complications. This article focuses on bringing physicians up-to-date on the most recent findings and discussions about the epidemiology, etiology, diagnosis, and treatment of acute septic arthritis. In recent years, the emergence of antibiotic-resistant, particularly aggressive bacterial species has highlighted the need for more research to enhance treatment approaches and develop innovative diagnosis methods and drugs that might combat better in all patients.This article aims to furnish radiologists, orthopaedic surgeons, and other medical practitioners with contemporary insights on the subject matter and foster collaborative efforts to improve patient outcomes. This review represents the initial comprehensive update encompassing patients across all age groups.